Spain : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2017)
This paper assesses the stability of the Spanish financial system as a whole. Spain's banking system has been steadily progressing since the last Financial System Assessment Program. The authorities have made a significant reform effort. Together with the economic recovery, and support by the European Central Bank's accommodative policies, the banking system has strengthened its solvency and advanced in reducing nonperforming loans. It is critical to keep the reform process moving and to build on the advances made during 2012-16. Completing the restructuring of bank balance sheets is a priority. Enhanced monitoring and supervisory attention to interest rate and liquidity risks are also merited.